If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(r + 7) = -90 Reorder the terms: -6(7 + r) = -90 (7 * -6 + r * -6) = -90 (-42 + -6r) = -90 Solving -42 + -6r = -90 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + -6r = -90 + 42 Combine like terms: -42 + 42 = 0 0 + -6r = -90 + 42 -6r = -90 + 42 Combine like terms: -90 + 42 = -48 -6r = -48 Divide each side by '-6'. r = 8 Simplifying r = 8
| 20=y-8.1 | | 2x-250=100 | | 9.16515139= | | 5a/5 | | 40+14d=2(-4d-13) | | 8.1+4=20 | | 2x+250=1000 | | 92+78+x=180 | | 49+x+3=90 | | x^2=-1/6 | | 8x-8=10x+7 | | -5x-6y=8 | | 1x+10=7t-14 | | 5(7x-8)=-329 | | 4x^4=324 | | 10000=6x+20 | | 10,000=6x+20 | | 6x+3=92 | | y-4=4(x-1) | | 5+2x=32 | | 3w-6=4.9 | | 3x+6=92 | | 0.28=ln(y) | | 72+x+4=180 | | 3a+2-6+5a= | | f^2+3f=12 | | 6-2(p+4)-2=0 | | 2(x-250)=1000 | | 2x=1-3(-.25x+1.5) | | 54.5=2x+2.3 | | X-0.4x=0.44x+2.4 | | -3g+7-3b=2 |